Metabolic Changes in Nicotinamide Adenine Dinucleotide in Response to Anthrax Toxin - Gray, Irving (1967)
Bacillus anthracis produces a toxin both in vitro and in vivo which, when injected intravenously into rats, brings about the death of the animals accompanied by gross pulmonary edema. Lung tissue removed prior to death showed, in vitro, a 30% reduction in overall oxidative metabolism (Q(o(2))), whereas the nicotinamide adenine dinucleotide (NAD)-independent succinic dehydrogenase remained unaffected. The NAD concentration in the lungs of injected animals was reduced by 50%. Upon addition of NAD, the Q(o(2)) of lung tissue from injected animals rose to control values. At 45 min after toxin injection, the serum lactate concentration began to rise, showing about a 3.5-fold increase over controls after 75 min. No changes occurred in the pyruvate concentration. These changes may be explained by increased use of the pyruvate for glycolytic energy production with further loss of NAD. Additional experiments with liver, spleen, kidney, and brain tissues showed that the toxin-induced reduction of Q(o(2)) is an effect specific for lung tissue. Brain tissue showed a significant increase in oxidative metabolism upon the addition of the toxin, whereas the other tissues remained unaffected. It is suggested that a principal effect of the toxin is to inhibit, in lung tissue, the regeneration of NAD in the respiratory chain.